"El poema Escotida o vida del Doctor Sutil Escoto" (1744), de fray Gregorio Farías, un antecedente americano del dogma de la Inmaculada Concepción - Álvarez, Rodrigo (2024)
Durante la época colonial, en algunos países de Iberoamérica, se desarrolló un movimiento teológico que tuvo como centro el pensamiento escotista. Si bien la complejidad de las ideas de este franciscano abarcó muchos aspectos de las verdades de fe, su impronta se manifestó claramente en un poema escrito por un religioso chileno: Gregorio Farías. Este, siguiendo los parámetros de la épica heroica de corte sacro, dio a luz una obra conocida como la "Scotida". Allí puso en valor el tema de la Inmaculada Concepción antes de su promulgación dogmática, abordando los ejes que justifica su inclusión en el depósito de la fe. Este estudio analiza los aspectos mariológicos más relevantes de esta obra, anterior a la bula Innefabilis Deus.
During the colonial period, a theological movement based on the thought of John Dons Scotus developed in some countries of the Spanish empire in the Americas. Although the complexity of this Franciscan’s thought covered many aspects of the truths of faith, his impact was clearly demonstrated in a long-form poem written by the Chilean monk Gregorio Farías. Farías penned Escotida following the style of a heroic epic with a sacred focus. In it, he explored the subject of the Immaculate Conception before its codification into dogma, addressing the key concepts that justify its inclusion in the repository of faith. This study analyzes the most relevant Mariological aspects of this epic poem, which predated the Innefabilis Deus bull.During the colonial period, a theological movement based on the thought of John Dons Scotus developed in some countries of the Spanish empire in the Americas. Although the complexity of this Franciscan’s thought covered many aspects of the truths of faith, his impact was clearly demonstrated in a long-form poem written by the Chilean monk Gregorio Farías. Farías penned Escotida following the style of a heroic epic with a sacred focus. In it, he explored the subject of the Immaculate Conception before its codification into dogma, addressing the key concepts that justify its inclusion in the repository of faith. This study analyzes the most relevant Mariological aspects of this epic poem, which predated the Innefabilis Deus bull.
Keywords: Duns Escoto; Gregorio Farías; Immaculate Conception; Inmaculada Concepción; Dogma; grace Scotida Inmaculada Concepciòn Dogma Gracias; Gracia; gracia Duns Scotus